Clinical Potential of Adrenomedullin Signaling in the Cardiovascular System. Issue 9 (28th April 2023) - Bálint, László; Nelson-Maney, Nathan P.; Tian, Yanna; Serafin, Stephen D.; Caron, Kathleen M.
Abstract : Numerous clinical studies have revealed the utility of circulating AM (adrenomedullin) or MR-proAM (mid-regional proAM 45-92) as an effective prognostic and diagnostic biomarker for a variety of cardiovascular-related pathophysiologies. Thus, there is strong supporting evidence encouraging the exploration of the AM-CLR (calcitonin receptor-like receptor) signaling pathway as a therapeutic target. This is further bolstered because several drugs targeting the shared CGRP (calcitonin gene-related peptide)-CLR pathway are already Food and Drug Administration-approved and on the market for the treatment of migraine. In this review, we summarize the AM-CLR signaling pathway and its modulatory mechanisms and provide an overview of the current understanding of the physiological and pathological roles of AM-CLR signaling and the yet untapped potentials of AM as a biomarker or therapeutic target in cardiac and vascular diseases and provide an outlook on the recently emerged strategies that may provide further boost to the possible clinical applications of AM signaling.